FAMILY CARING CAPITAL AS THE LATEST INSTRUMENT OF NATIONAL FAMILY POLICY - Krawczyk, Michał (Management and Administration Journal, 2022)
On 17 November 2021, the Law on the Family Caring Capital was passed. It introduced, alongside existing family-friendly programmes such as "Family 500+" and " The Good Start", a new programme in the form of the Family Caring Capital. The article defined the concept of family policy. Current demographic problems were discussed. The assumptions and objectives of the Family Caring Capital Programme were analysed. An attempt has also been made to answer the question as to what extent it will fulfil the hopes placed in it regarding an increase in childbirths in Poland.